2021
DOI: 10.3389/fonc.2021.747282
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone Selectively Kills Hepatocellular Carcinoma Cells by Targeting NQO1 to Induce Extensive DNA Damage and PARP1 Hyperactivation

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death globally. Currently there is a lack of tumor-selective and efficacious therapies for hepatocellular carcinoma. β-Lapachone (ARQ761 in clinical form) selectively kill NADPH: quinone oxidoreductase 1 (NQO1)-overexpressing cancer cells. However, the effect of β-Lapachone on HCC is virtually unknown. In this study, we found that relatively high NQO1 and low catalase levels were observed in both clinical specimens collected from HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Additionally, while NQO1:CAT was not directly measured, inhibition of catalase and GSH did not lead to a sensitization of KEAP1-mutated NSCLC during −lapachone treatment while inhibition of TXNRD and SOD1 sensitized cancers (28). A recent TCGA analysis revealed higher NQO1:CAT levels in hepatocellular carcinoma (HCC) than in matched healthy tissue, and the authors reported that the high NQO1 patient cohort had lower survival (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while NQO1:CAT was not directly measured, inhibition of catalase and GSH did not lead to a sensitization of KEAP1-mutated NSCLC during −lapachone treatment while inhibition of TXNRD and SOD1 sensitized cancers (28). A recent TCGA analysis revealed higher NQO1:CAT levels in hepatocellular carcinoma (HCC) than in matched healthy tissue, and the authors reported that the high NQO1 patient cohort had lower survival (37).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while NQO1:CAT was not directly measured, inhibition of catalase and GSH did not lead to a sensitization of KEAP1-mutated NSCLC during β–lapachone treatment while inhibition of TXNRD and SOD1 sensitized cancers (28). A recent TCGA analysis revealed higher NQO1:CAT levels in hepatocellular carcinoma (HCC) than in matched healthy tissue, and the authors reported that the high NQO1 patient cohort had lower survival (37). These studies serve to highlight the complexity of the antioxidant system in the context of NQO1-activatable drugs like β–lapachone, and suggest the current approach for identifying how well a cancer would respond to the treatment is underdeveloped.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Nqo1 has been observed in HCC and enhances the vulnerability of cells to oxidative stress-induced injury. Nqo1 is also involved in regulating the proliferative and aggressive characteristics of HCC [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manganese porphyrin enhances NRF2 in the normal tissue only (Shrishrimal et al, 2017;Chatterjee et al, 2020), which helps to sustain the natural anticancer activity of normal cells and increase anticancer treatment efficacy. β-Lapachone senses the NQO1 levels in the tissue and inhibits NRF2 signaling to maintain homeostasis (Gong Q et al, 2021;Wu et al, 2021;Zhao et al, 2021). As the advanced PCa tissue harbors enhanced NRF2-NQO1 levels as compared to the normal prostate tissue, to cope with increased oxidative stress, β-Lapachone may have a better efficacy to reduce NRF2 selectively in cancer tissue.…”
Section: Nrf2 Modulators In Anticancer Clinical Trialsmentioning
confidence: 99%